The Relationship of Parents' Divorce and Self-Acceptance of Students of High School, Tegalwaru District, Karawang Regency Class 12, Force of 2022 - Nurmawati Nurmawati; Fila Hasan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research was conducted to know the process of self-acceptance of high school students in Tegalwaru District, Karawang Regency, who experienced parental Divorce and know the nature and positive attitudes of students towards themselves in order to become happy human beings in the future. This research was conducted on 12th-grade students of Tegalwaru District, Karawang Regency, Class of 2022, including SMAN 1 Tegalwaru, Integrated Islamic High School Tahfidzul Nurul Qur'an, and MA Miftahul Huda. This research was conducted from November 2021 – to April 2022 with quantitative research and a descriptive approach. The sample collection used was simple random sampling with a total sample of 68 students. The type of instrument used is a questionnaire or questionnaire with a Likert scale in the form of an assessment score interval of 1-4, which will be analyzed using SPSS 23. Based on the results of research conducted at SMA Tegalwaru District, Karawang Regency, the results were in the form of the highest divorce score at 120 and the lowest score at 30 which means that the data is normally distributed, the highest self-acceptance score is 240, and the lowest score is 60 which means the data is not normally distributed, normality test with a significance value of 0.200 > 0.05 which means the residual value is normally distributed, linearity test of Sig. Deviation from linearity 0.000 < 0.05, which means that there is no linear relationship between Divorce and self-acceptance, the correlation value of R square is 0.528, which means that the influence of the independent variable (Divorce) on the dependent variable (self-acceptance) is 52.8%, the value of constant (a) is 58.122 with the value of b/regression coefficient is 0.621 which means the direction of the influence of the X variable on Y is positive, the significance value of the coefficients table is 0.000 < 0.005 which means that the divorce variable is related to the self-acceptance variable, and the t value is 5.598 > table 2.037 which means that the divorce variable is related to the acceptance variable.